Blood metabolites as indicators of energy status in goats - Fernández J.R.; Ramos E.; De la Torre G.; Hermoso R.; Gil Extremera F.; Sanz Sampelayo M.R. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
With the aim to identify the blood metabolites that are most indicative of the animal's energy status, an experiment was carried out with two groups of six uncastrated male growing goats of the Granadina breed. As well as the intake of metabolisable energy, plasma concentrations of glucose, non-esterified fatty acids, triglycerides and ß-hidroxybutirate were measured. A multivariate factorial analysis was performed to establish the patterns of relationships between the different variables. From the results obtained it was deduced that the plasma concentration of non-esterified fatty acids presented the closest relation with the intake of metabolisable energy, being capable in itself of indicating the animal's energy status.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)